Food Sovereignty For Indonesia: The Epistemological Dimension of Knowledge and Variety of Local Food - Sugeng Sugeng; Annisa Fitria (Jurnal Analisis Hukum, 2023)
This article aims to emphasize that food sovereignty policies require the support of knowledge that is not singular.  Epistemological diversity is believed to produce richer and more contextual knowledge of the needs of local communities.  In the process of formulating public policies, scientific knowledge needs to be paired with local knowledge developed through oral traditions. This approach is in accordance with the geographical conditions and natural resources of Indonesia, which has a rich biodiversity and diversity of foodstuffs in various regions.  Indonesia's ethnic diversity and biodiversity are advantages that need to be maintained for sustainable food sovereignty. This philosophical study is useful as a basis for compiling a more comprehensive food sovereignty legal framework.